2014
DOI: 10.1038/bjc.2014.96
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus among oesophageal squamous cell carcinoma cases: systematic review and meta-analysis

Abstract: Background:Oncogenic human papillomavirus (HPV) has been hypothesised as a risk factor for oesophageal squamous cell carcinoma (OSCC), but aetiological research has been limited by the varying methodology used for establishing HPV prevalence. The aims of this systematic review and meta-analysis were to estimate the prevalence of HPV DNA detected in OSCC tumours and the influence of study characteristics.Methods:Study-level estimates of overall and type-specific HPV prevalence were meta-analysed to obtain rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 58 publications
(78 reference statements)
8
85
1
Order By: Relevance
“…With respect to esophageal cancer, studies also reported that HPV 16 was the main HPV type (Yong et al, 2013;Li et al, 2014;Petrick et al, 2014), although there is a controversy on this issue. Meta-analysis conducted by Petrick et al showed that HPV 16 prevalence ranged from 17.3% to 35.9% in esophageal cancer using different detecting method (Petrick et al, 2014). Yong et al also reported that the prevalence of HPV 16 in esophageal cancer was 11.7% (Yong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to esophageal cancer, studies also reported that HPV 16 was the main HPV type (Yong et al, 2013;Li et al, 2014;Petrick et al, 2014), although there is a controversy on this issue. Meta-analysis conducted by Petrick et al showed that HPV 16 prevalence ranged from 17.3% to 35.9% in esophageal cancer using different detecting method (Petrick et al, 2014). Yong et al also reported that the prevalence of HPV 16 in esophageal cancer was 11.7% (Yong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the HPV as oncogenes or co-factors in the carcinogenesis of EC has been reported in the last 30 years (Petrick et al, 2014), especially combinative study of HPV infection rate on EC and cervical cancer tumor samples in geographic areas with a high incidence of EC (Zhang et al, 2010;Liu et al, 2014). According to epidemiologic classification, at least 15 oncogenic HPV types were found in cervical precancerous lesions and carcinoma, of which HPV16 and HPV18 were the most prevalent high-risk types worldwide, whereas HPV-58 has been found in a relatively higher proportion in eastern Asia .…”
Section: Introductionmentioning
confidence: 99%
“…EpsteinBarr virus (EBV) has a long history of generating tumors, which is specifically known as the causative agent of Burkitt's lymphoma, nasopharyngeal carcinoma, breast carcinomas and hepatocellular carcinomas (6,(55)(56)(57)(58). Human papillomavirus (HPV) is a DNA virus containing a large genome of the papilloma virus family, which is known as the etiological agent of cervical cancer (59)(60)(61)(62)(63)(64)(65). Several studies reported that smoking and alcohol synergistic effects may lead HPV infections to one of the major risk factors for cancer in oral cavity (6.…”
Section: Association Of Microorganisms In the Development Of Cancermentioning
confidence: 99%